Implementation of the Merdeka Curriculum in Shaping the Character of Teachers at SMAN 1 Namorambe and SMAN 1 Kutalimbaru - Siregar, Abdul Hamid; Mesiono, Mesiono; Abdurrahman, Abdurrahman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study explores how the implementation of the Independent Curriculum (Kurikulum Merdeka) influences teacher character formation in two public senior high schools SMA Negeri 1 Namorambe and SMA Negeri 1 Kutalimbaru through a multisite qualitative approach. Data were collected through interviews, observations, and document analysis to identify differences in understanding, practices, and contextual factors affecting curriculum application. The findings reveal that both schools share a fundamental understanding of the Independent Curriculum’s core principles flexibility, differentiated learning, and strengthening the Pancasila Student Profile (P5) yet their implementations differ significantly. At SMA Negeri 1 Namorambe, the curriculum is primarily viewed as an administrative requirement, emphasizing discipline, responsibility, and individual independence. Conversely, SMA Negeri 1 Kutalimbaru interprets it as a framework for creativity, collaboration, and contextual learning, fostering innovative, reflective, and socially aware teacher characteristics. Contextual factors such as leadership style, socio-cultural environment, and resource availability play a critical role in shaping these outcomes. The study concludes that participatory leadership and a culture of collaboration enhance curriculum effectiveness and teacher character growth, while administrative rigidity and limited resources constrain innovation. Overall, the Independent Curriculum demonstrates flexibility, enabling diverse pathways to professional and character development among teachers across different school settings.